Kształcenie ekonomiczne w dotychczasowej i postulowanej ewolucji systemu gospodarczego - Wierzbicki, Janusz (Wydział Prawa i Administracji UAM, 1987)
The author distinguishes between four models of economic education in a socialist state, corresponding with the conditions of: market economy, centralized economy, mixed economy — where elements of centralized management prevail yet directival management is replaced by quasi-parametric management. The author considers engineering-economical studies as a separate model since the latter type is not so strongly connected with the economic system. Besides, the author analyses the demand for economists, characterizes its evolution in years 1950 - 1985 and concludes that the greatest demand has been and still is for economists-clerks, prepared to work in definite branches and occupying posts which often do not require university education at all. Much less demand is for economists-technocrats, prepared to occupy managerial positions in independent enterpries and the least demand is for highly qualified economists-managers. The latter phenomenon results from the attitudes of economic decision-makers rather than from the needs of economic reform and the slow economic evolution adds to that trend. The author is of the opinion that the system of economic training should be based on model solutions corresponding with future needs of the reformed economy with adjustements resulting from actual demand for economists; all this may lead to dualism in economic education. Supplementing the above considerations the author analyses the role of student professional apprenticeships in economic education. He points out to inappropriate conditions for such apprenticeships in economic units and he concludes that the solution of the problem of student apprenticeships should depend on the improvement of those conditions with the decision concerning the organization of such apprenticeships left to the school alone.
Economic education in the hitherto existing and postulated evolution of the economic system